The mechanism of body appreciation influencing social anxiety in college students: A moderated mediation model - Jinwei Zhu; Zhenming Jiang; Yan Li; Yani Cai; Jiayu Chen (Acta Psychologica)
This study examines the impact of body appreciation on social anxiety among college students, focusing on the mediating role of social suspiciousness and the moderating role of self-congruency in the relationship between body appreciation and social suspiciousness. An analysis of data from 1161 questionnaires reveals that body appreciation is a significant negative predictor of social anxiety among college students. Furthermore, body appreciation indirectly influences social anxiety through social suspiciousness. Additionally, self-congruency significantly moderates the relationship between body appreciation and social suspiciousness. Specifically, a positive perception of one's body—appreciating its uniqueness and functionality, and positively processing and protecting body-related evaluative information—can directly reduce social anxiety. It can also indirectly reduce social anxiety by lowering social suspiciousness in interpersonal settings. Moreover, self-congruency plays a moderating role in the pathway from body appreciation to social suspiciousness. The findings of this study offer new insights into the relationship between body appreciation and social anxiety among college students. By enhancing self-congruency, the negative impact of low body appreciation on social anxiety can be lessened, providing important practical implications for developing effective interventions to address social anxiety in college students.